Aliivibrio salmonicida requires O-antigen for virulence in Atlantic salmon (Salmo salar L.). (November 2018) - Nørstebø, Simen Foyn; Lotherington, Leif; Landsverk, Marius; Bjelland, Ane Mohn; Sørum, Henning
Abstract: Aliivibrio salmonicida is the causative agent of cold-water vibriosis, a hemorrhagic septicemia of salmonid fish. The bacterium has been shown to rapidly enter the fish bloodstream, and proliferation in blood is seen after a period of latency. Although the pathogenesis of the disease is largely unknown, shedding of high quantities of outer-membrane complex VS-P1, consisting of LPS and a protein moiety, has been suggested to act as decoy and contribute to immunomodulation. To investigate the role of LPS in the pathogenesis, we constructed O-antigen deficient mutants by knocking out the gene encoding O-antigen ligase waaL . As this gene exists in two copies in the Al. salmonicida genome, we constructed single and double in-frame deletion mutants to explore potential effects of copy number variation. Our results demonstrate that the LPS structure of Al. salmonicida is essential for virulence in Atlantic salmon. As the loss of O-antigen did not influence invasive properties of the bacterium, the role of LPS in virulence applies to later stages of the pathogenesis. One copy of waaL was sufficient for O-antigen ligation and virulence in experimental models. However, as a non-significant decrease in mortality was observed after immersion challenge with a waaL single mutant, it is tempting to suggest that multiple copies of the gene are beneficial to the bacterium at lower challenge doses. The loss of O-antigen was not found to affect serum survival in vitro, but quantification of bacteria in blood following immersion challenge suggested a role in in vivo survival. Furthermore, fish challenged with the waaL double mutant induced a more transient immune response than fish challenged with the wild type strain. Whether the reduction in virulence following the loss of waaL is caused by altered immunomodulative properties or impaired survival remains unclear. However, our data demonstrate that LPS is crucial for development of disease. Highlights: LPS structure is essential for the virulence of Al. salmonicida. Invasion of Atlantic salmon does not depend on LPS. LPS contributes to the immune response raised towards Al. salmonicida.